Research-training as an act of re-existence of teachers before and during the pandemic (Revista Internacional de Formação de Professores, 2023)
This article seeks to analyze the research-formation through the qualitative approach in two distinct research and to relate it to the acts of re-existence explaining how this process was consolidated during the pandemic. This proposal is based on the studies of Macedo (2007); Behrens (2007); Paim (2012); Martins (2014). Re-existence acts aim to promote moments that comply with each teacher's subjectivities enabling the expansion of their inventiveness and creativity so that the teacher can share new opportunities among their peers so that they are the defining self-forming that aims to resist a project who aims to standardize the current teacher education.
Keywords: Teacher education. Re-existence acts. Research-formation. Qualitative approach.